Cryptocurrency price prediction and forecasting using machine learning algorithm and long- short term memory mapping - Zaman, Md. Sayeed Ibne; Kamal, Mir Ishraq; Ishan, Samiu Mostafa; Khan, Shafayat Zamil; Hossain, Samiha (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.